Framing Media dalam Pemberitaan Longsor Kabupaten Bandung Barat pada Media Online - Sabila Lestiasih Gunadi; Guruh Ramdani (CV. ITTC INDONESIA, 2026)
This study is motivated by the differences in media framing in reporting the landslide disaster in West Bandung Regency by the online media Mongabay and TvOneNews. These differences can be seen in the way the media select issues, emphasize facts, and construct social reality in disaster reporting. The media not only convey information, but also shape public perception through the use of language and the emphasis on certain aspects of the news. This study aims to analyze media framing in reporting the landslide disaster in West Bandung Regency by the online media Mongabay and TvOneNews. This study employs a qualitative descriptive method using Robert N. Entman’s framing analysis approach. The analysis technique is conducted through four framing elements, namely define problems, diagnose causes, make moral judgement, and treatment recommendation. The research data consist of news texts regarding the landslide disaster in Cisarua, West Bandung Regency, published by both media outlets between January and February 2026. The findings show that Mongabay frames the landslide as a structural issue related to environmental damage, land-use change, weak spatial planning, and inadequate government supervision. Meanwhile, TvOneNews emphasizes the personalization of leadership through the representation of Dedi Mulyadi as an empathetic, responsive, and community-oriented figure toward disaster victims. These framing differences indicate that the media play an important role in shaping public perceptions of disaster events.